Oxidation mechanism of thin Cu films: A gateway towards the formation of single oxide phase - Choudhary, Sumita; Sarma, J. V. N.; Pande, Surojit; Ababou-Girard, Soraya; Turban, Pascal; Lepine, Bruno; Gangopadhyay, Subhashis (AIP advances, 2018)
Controlled thermal oxidations of thin copper films at relatively lower temperatures (up to 500°C) leading towards the formation of a single phase of copper oxide are investigated where the oxidation temperature, duration, oxygen partial pressure, film thickness and the crystallographic orientations play very crucial roles to significantly control the final phase of the copper oxide. Thin Cu films of thicknesses 100-1000 nm were deposited on glass and silicon substrates using the vacuum assisted thermal evaporation technique. Oxidations of those Cu films were performed at different temperatures for variable durations in air ambient as well as oxygen ambient conditions. Four probe resistivity measurement, x-ray diffraction (XRD), Raman spectroscopy, ultraviolet–visible (UV-Vis) spectroscopy, scanning electron microscopy (SEM) and x-ray photoemission spectroscopy (XPS) techniques have been used to characterize the oxide films. At a thermodynamic equilibrium, it has been observed that the oxide phase is solely determined by the oxidation temperature, however, the oxygen partial pressure can significantly alter this temperature range. In case of thermal oxidation in air, the initial oxidation of the copper films starts at about 150 °C, but a well ordered crystalline phase of the cuprous oxide (Cu2O) is observed only above 200 °C. However, the cupric oxide (CuO) phase starts to appear only above 320 °C. The details of the oxidation mechanism of the Cu film are explained with a probable schematic model in terms of thermal diffusion as well as the chemical reactivity.